2021
DOI: 10.17221/88/2020-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics of native conifer species in Vietnam based on two chloroplast gene regions rbcL and matK

Abstract: We used two chloroplast gene regions (matK and rbcL) as a tool for the identification of 33 local conifer species. All 136 sequences, 101 newly generated (14 species for gene matK; 16 species for gene rbcL) and 35 retrieved from the GenBank, were used in the analysis. The highest genetic distance (matK region) was recorded between the species in Cupressaceae with an average of 5% (0.1–8.5), Podocarpaceae with an average of 6% (0–8.5), Taxaceae with an average of 5% (0.2–0.5) and Pinaceae with an average of 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Te latter region evolves slowly and is, therefore, used more frequently in phylogenetic analyses [30]. In addition, the rbcL gene is a more universal region and is less efcient in separating closely related taxa [16], although some studies on angiosperm species have shown that this region presents enough variation to distinguish species [31]. Meanwhile, matK, which presents a faster evolution, is widely used for phylogenetic analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te latter region evolves slowly and is, therefore, used more frequently in phylogenetic analyses [30]. In addition, the rbcL gene is a more universal region and is less efcient in separating closely related taxa [16], although some studies on angiosperm species have shown that this region presents enough variation to distinguish species [31]. Meanwhile, matK, which presents a faster evolution, is widely used for phylogenetic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, given the high conservation of its sequence, compact size, lack of recombination, and maternal inheritance, the chloroplast genome has been used for the generation of genetic markers and for phylogenetic classifcation [13], genetic divergence [14], and DNA barcoding systems for molecular identifcation [15]. Commonly studied chloroplast coding genes include atpF-atpH, matK, rbcL, rpoB, rpoC1, psbK-psbL, and trnH-psbA since they meet the requirements for use as DNA barcodes in plants [16]. Hollingworth et al (2009) recommended the combination of two loci, ribulose-1,5-bisphosphate carboxylase (rbcL) and maturase (matK), as a plant barcode based on assessments of recoverability, sequence quality, and levels [17].…”
Section: Introductionmentioning
confidence: 99%
“…For greater plant group resolution, it is interesting to note that numerous scientists have suggested merging different barcoding sites or entire chloroplast genome sequences [48,49]. Several authors have demonstrated the utility of single barcoding loci to differentiate between plant species, including conifers [50] and bamboo [51], wild cherry [52], and zingiber [53]. The results showed that each individual and combination of loci raised the level of discrimination between selected mangrove species.…”
Section: Discussionmentioning
confidence: 99%
“…Wall. genus Dacrydium (Podocarpaceae) isconifer species in Vietnam, grows in primary closed evergreen seasonal forest tropical mixed (elevations 700-2000m) they have been extensively used for furniture, handicrafts and construction [1][2][3]. In Vietnam it is found in Ha Giang, Tuyen Quang, Quang Ninh, Lai Chau, Ha Tinh, Quang Binh, Thua Thien Hue, Da Nang, Kon Tum, Gia Lai, Dak Lak, Lam Dong and Kien Giang provinces and other countries like China, Laos, Cambodia, Thailand, Malaysia and Indonesia [1][2].…”
Section: Introductionmentioning
confidence: 99%